KNOWLEDGE AND PERCEPTION OF HAND HYGIENE AMONG HEALTH CARE WORKERS OF A TERTIARY CARE MILITARY HOSPITAL: A DESCRIPTIVE STUDY: Hand Hygiene Among Health Care Workers - Iqbal, Mahmood; Zaman, Muhammad; Azam, Naila (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the knowledge and perception of doctors and paramedical staff about hand hygiene of a tertiary care military hospital. Study Design: Cross sectional descriptive study. Place and Duration of Study: Study was conducted at tertiary care military hospital, from Aug 2016 to Jan 2017. Material and Methods: The sample size 196 was calculated using World Health Organization sample size calculator. Permission from administrative authorities was taken. Purposive sampling technique was used. World Health Organization’s knowledge and perception structured self-administered questionnaire was used with minor amendments for the data collection. The percentage’s in knowledge and perception domain of >75% determined good, 50-75% fair and <50% poor. Results: There were 88 (45%) paramedical staff, 49 (25%) doctors and 59 (30%) nurses while overall 103 (52.5%) were male and 93(47.5%) female. The age of 160 (81.5%) study participants ranged 21-40 years. The overall mean score of knowledge was 64.1% and perception 72.5%. The paramedical staff presented with lowest mean score in knowledge 60.6% and perception 74.9%. While doctors scored highest 64.6% in knowledge domain and nurses scored highest in perception domain 82.2%. There was no statistical significant difference of knowledge and perception of hand hygiene between and within doctors, nurses and paramedical staff knowledge (p-value 0.799 and p-value 0.515 respectively). Conclusion: The overall knowledge and perception of study participants about hand hygiene was fair. However, doctorsand nurses’ perception of hand hygiene was good.